PNEUMOCOCCAL INFECTION IN CHILDREN: OPPORTUNITIES OF PROPHYLAXIS - S.M. Kharit (Вопросы современной педиатрии, 2009)
The article is dedicated to the actual problem of modern health care — pneumococcal infections and opportunities of its prophylaxis. Authors describe risk groups of development of invasive pneumococcal infections. A characteristics of available at the present times in Russia and all over the world vaccines, including pneumococcal 7-valent vaccine (PCV7) Prevenar, intended to the prophylaxis of pneumococcal infections in children under the age 2 months — 5 years old. An experience of PCV7 use in the world in analyzed. The article gives an estimation of perspectives of inclusion of PCV7 to the national immunizations schedule.Key words: children, pneumococcal infections, prophylaxis, pneumococcal conjugated 7-valent vaccine.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(5):62-69)